Beban Kognitif Mahasiswa dalam Pembelajaran Daring di Masa Pandemi Covid-19 - Santi Wahyuni; Yanti Cahyati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Online learning during the pandemic was adopted as a government policy to prevent the spread of covid-19. The various limitations and obstacles faced during the online learning process during the pandemic require adaptation from both educators and students. Students need to make adjustments in learning and educators to manage cognitive load in learning. The research objective was to describe the cognitive load of students in online learning during the Covid-19 pandemic. This descriptive study involved 316 respondents. The data collection process was carried out online. The results of data analysis showed that the majority of respondents had a moderate cognitive load (73.1%). Based on the type of cognitive load, it was known that most respondents have moderate ICL (66.8%), moderate ECL (71.8%) and all respondents have moderate GCL (100%). Based on the research results, it is expected that lecturers can optimize student abilities and make efforts to improve learning strategies to reduce student cognitive load. Keywords: cognitive load; intrinsic cognitive load; extraneous cognitive load; germane cognitive load ABSTRAK Pembelajaran daring di masa pandemi ditempuh sebagai kebijakan yang dilakukan pemerintah untuk mencegah penyebaran covid-19. Berbagai keterbatasan dan kendala yang dihadapi selama proses pembelajaran daring di masa pandemi menuntut adaptasi baik dari pendidik dan peserta didik. Mahasiswa perlu melakukan penyesuaian diri dalam belajar dan pendidik melakukan pengelolaan beban kognitif dalam pembelajaran. Tujuan penelitian untuk mendeskripsikan beban kognitif mahasiswa dalam pembelajaran daring di masa pandemi covid-19. Penelitian deskriptif ini melibatkan 316 responden. Proses pengumpulan data dilakukan secara daring. Hasil analisa data menunjukkan mayoritas responden memiliki beban kognitif kategori sedang (73,1%). Berdasarkan jenis beban kognitif, diketahui sebagian besar responden memiliki ICL kategori sedang (66,8%), ECL kategori sedang (71,8%) dan seluruh responden memiliki GCL kategori sedang (100%). Berdasarkan hasil penelitian, diharapkan dosen dapat mengoptimalkan kemampuan mahasiswa dan melakukan upaya perbaikan strategi pembelajaran untuk menurunkan beban kognitif mahasiswa. Kata kunci: beban kognitif; intrinsic cognitive load; extraneous cognitive load; germane cognitive load